Impact of melatonin supplementation on sports performance and circulating biomarkers in highly trained athletes: A systematic review of randomized controlled trials - San Miguel, A. M. C.; Roche, E.; Herranz-López, M.; San Miguel, M. C.; Mielgo-Ayuso, J.; Fernández-Lázaro, D. (Nutrients, 2024)
Melatonin (N-acetyl-5 methoxytryptamine) is an indolic neurohormone that modulates a variety of physiological functions due to its antioxidant, anti-inflammatory, and immunoregulatory properties. Therefore, the purpose of this study was to critically review the effects of melatonin supplementation in sports performance and circulating biomarkers related to the health status of highly trained athletes. Data were obtained by performing searches in the following three bibliography databases: Web of Science, PubMed, and Scopus. The terms used were "Highly Trained Athletes", "Melatonin", and "Sports Performance", "Health Biomarkers" using "Humans" as a filter. The search update was carried out in February 2024 from original articles published with a controlled trial design. The PRISMA rules, the modified McMaster critical review form for quantitative studies, the PEDro scale, and the Cochrane risk of bias were applied. According to the inclusion and exclusion criteria, 21 articles were selected out of 294 references. The dose of melatonin supplemented in the trials ranged between 5 mg to 100 mg administered before or after exercise. The outcomes showed improvements in antioxidant status and inflammatory response and reversed liver damage and muscle damage. Moderate effects on modulating glycemia, total cholesterol, triglycerides, and creatinine were reported. Promising data were found regarding the potential benefits of melatonin in hematological biomarkers, hormonal responses, and sports performance. Therefore, the true efficiency of melatonin to directly improve sports performance remains to be assessed. Nevertheless, an indirect effect of melatonin supplementation in sports performance could be evaluated through improvements in health biomarkers.